Effects of intracerebroventricular application of insulin-like growth factor 1 and its N-terminal tripeptide on cerebral recovery following cardiac arrest in rats - Knapp, Jürgen; Teschendorf, Peter; Vogel, Peter; Bruckner, Thomas; Popp, Erik (Resuscitation, 2013)
Background Following global cerebral ischaemia due to cardiac arrest (CA), selective neuronal vulnerability and delayed neuronal death with distinct signs of apoptosis could be observed in certain areas of the brain. Growth hormones like the insulin-like growth factor 1 (IGF-1) and the bioactive N-terminal tripeptide of IGF-1, glycine-proline-glutamate (GPE), exhibit strong protective properties in focal ischaemia in vivo and in vitro. To examine these promising effects on neuronal survival and cerebral recovery after experimental cardiopulmonary resuscitation, the most vulnerable hippocampal CA-1 sector was investigated.Methods After 6min of CA, 54 male Wistar rats were resuscitated and were randomly assigned to 3 groups (IGF-1, GPE vs. placebo; n=6 per group) and 3 different reperfusion periods. Intracerebroventricular application of IGF-1 (1.25μgh−1), GPE (50ngh−1) and placebo was performed using osmotic minipumps up to day 7 following reperfusion. After 3, 7 and 14 days, coronal brain sections were analysed by counting Nissl-positive (i.e. viable) neurons and TUNEL-positive (i.e. apoptotic) cells. All experiments were performed in a randomised and blinded setting.Results In all groups in the hippocampal CA-1 sector typical delayed neurodegeneration from day 3 to day 14 after CA could be found. No significant increase of the number of Nissl-positive neurons after IGF-1-treatment (p=0.18) as well as after GPE-treatment (p=0.14) could be observed. The number of TUNEL-positive cells could not be reduced significantly in the IGF-1 group (p=0.13), whereas GPE treatment revealed significant less TUNEL-positive cells (p=0.02). This was primarily an effect in the early phase (day 3: p=0.02) of reperfusion and was no more detectable 7 days (p=0.69) and 14 days after ROSC (p=0.30).Conclusion Despite the well known neuroprotective properties of IGF-1 and GPE in ischaemic induced neuronal degeneration, this model could only reveal a short-term beneficial effect of GPE after experimental cardiac arrest in rats. (Institutional protocol number: 35-9185.81/43/00.)